Frequency of Pre-Eclampsia in Obese Primigravida Compared to Non-Obese Primigravida - Tanzila Rafiq, Sidra Altaf, Piya Muhammad Musammat Rafi, Khozama Khan, Madiha Gillani, Samreen Akram, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to compare the prevalence of pre-eclampsia in obese primigravida compared to those who are not obese. Study Design: Prospective cohort study Place and Duration of Study: The research was conducted at the Gynecology and Obstetrics Department at the bahawal Victoria hospital Bahawalpur from 01 June 2021 to 31 December 2021. Materials and Methods: The study consisted of sixty (60) patients, selected using a non-probability consecutive sampling technique. All primigravida between the ages of 20 and 35, with singleton pregnancies of >26 weeks and with a BMI>30kg/m2 in the obese group and BMI<30kg/m2 in the non-obese group, were included. This data was collected on a specially designed Performa. An analysis of the data was conducted using SPSS version 16. Frequency and percentage were calculated for qualitative variables, such as pre-eclampsia (present/absent). Using Chi-square, we compared the frequency of pre-eclampsia. A p-value <0.05 was considered significant. Results: The range of age of participants in the study ranged from 20 to 35 years, with a mean age of 27.08 ± 3.59 years. The mean gestational age was 34.65 ± 4.35 weeks. The mean BMI in group A was 37.50 ± 5.47 kg/m2, while in group B it was 26.77 ± 3.64 kg/m2. The frequency of preeclampsia in Group A (obese primigravida group) was 43.33% (13%), while in group B (non-obese primigravida group) it was 13.33% (4%). Conclusion: The results of this study suggest that the frequency of preeclampsia in obese primigravida is higher compared to non-obese primigravida (43.33% versus 13.33%). This shows that obesity is a risk factor for preeclampsia and that there exist a positive relation between BMI and preeclampsia. Keywords: Obese Primigravida, Pre-eclampsia, Eclampsia, Risk Factors for Pre-eclampsia – Eclampsia, High risk pregnancy, Complicated during pregnancy. Obesity and Pregnancy.